Flexible PVDF membranes with exceptional robust superwetting surface for continuous separation of oil/water emulsions. Issue 1 (December 2017) - Xiong, Zhu; Lin, Haibo; Liu, Fu; Xiao, Peng; Wu, Ziyang; Li, Tiantian; Li, Dehong
Abstract Instability of superwetting surface is the stumbling block of flexible polymeric membranes for continuous separation of water-in-oil or oil-in-water emulsions. Manipulation of rigid superwetting nano-TiO2 on hierarchical poly(vinylidene fluoride) (PVDF) membrane by mimicking the plant roots holding soil behaviour enabled the generation of robust superwetting surface withstanding the harshly physical and chemical torture. The unique interface combination, which fabricated by a compacted nano-layer with the thickness of ~20 μm, was disclosed by systematic structure characterization. As demonstrated by SEM, LSCM and nano-CT, the pristine PVDF membrane with large quantities of cilia-like micro/nano-fibrils can function as the plant roots to capture, cage and confine the nanoparticles to form a robustly rigid nano-coating. The as-prepared membranes showed excellent durable separation performance both in varieties of stabilized water-in-oil and oil-in-water emulsion separation for a long term with few nanoparticles loss in a continuous crossflow mode. The strategy of assembling rigid inorganic nano-particles on flexible surface offers a window of opportunity for preparation of robust organic-inorganic hybrid membranes not only for continuous oil/water emulsion separation, but also for other functional application, such as electric conduction, heat conduction, ion exchange, and in membrane catalytic reactors etc.